Nexus between Capital Inflow and Economic Growth: Evidence from Indonesia - Jacobus Cliff Diky Rijoly,; Kangwook Noh,; I Putu Yoga Bumi Pradana, (Asian Academy of Management Journal of Accounting and Finance, 2025)
This research aims to examine the impact of capital inflow, specifically Foreign Direct Investment (FDI) and Portfolio Investment, on economic growth in Indonesia as an emerging market country. The study uses quarterly time series data from 2004 to 2021 and employs the Vector Error Correction Model (VECM) method to analyse the relationship between capital inflow and economic growth. The results show that FDI has a substantial impact on GDP in the short to middle term, while portfolio investment does not contribute as expected to boost economic growth. The instability of Indonesian political conditions and the U.S. economy’s power could create “crowd out” when economic shocks occur. The forecasting analysis result of the main interest variable (FDI and PortfolioInvestment) shows that Indonesian GDP will increase yearly in the long term, while Foreign Direct Investment and Portfolio Investment have a steady growth condition. This article contributes to the ongoing academic debate about the relationship between capital inflow and economic growth, as previous literature shows different results in developed and developing nations. The research will contribute to answering the question of how capital inflow plays a role in growing economies such as Indonesia in the long term.